Criminal procedure and sentencing - Hungerford-Welch, Peter (Routledge, Taylor and Francis Group, an informa business, 2019)
Criminal Procedure and Sentencing provides a comprehensive, engaging and up-to-date guide to each step of criminal procedure, from the arrest of the suspect through to trial, sentencing and appeals. Taking a strong practical focus throughout, it covers all aspects of the process of the criminal courts. The ninth edition has been fully revised and significantly expanded to include more information about the workings of the criminal courts of England and Wales. The supporting website offers readers access to regular updates to the law and also a comprehensive set of web links and advice on additional reading and research for those seeking to engage in critical evaluation of the criminal justice system. This is an ideal text for anyone studying the criminal justice system at a professional or academic level. The author's authoritative yet engaging writing style brings the subject to life and helps to explain complex issues in an easy-to-understand way.